Sounding out life in the deep using acoustic data from ships of opportunity - K. Haris (Nature Portfolio, 2021)
Measurement(s) bioacoustic data • sound quality Technology Type(s) echosounder • data processing software Sample Characteristic - Organism macro-zooplankton • micronekton Sample Characteristic - Environment ocean Sample Characteristic - Location Tasman Sea • Southern Ocean • Indian Ocean • South Pacific Ocean • North Pacific Ocean • Coral Sea • North Atlantic Ocean Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13172516